Structure of the protein encoded by the chicken proto-oncogene c-myb. - Gerondakis, S (1986)
The retroviral oncogene v-myb arose by transduction of the chicken proto-oncogene c-myb. We isolated and sequenced cDNA that represents the entire coding domain of chicken c-myb. By transcribing the cDNA into mRNA in vitro and then translating the RNA, we were able to document the integrity of the cDNA and to identify the codon responsible for initiation of translation from c-myb. Two different alleles of v-myb are extant, one in the genome of avian myeloblastosis virus (AMV) and the other in the genome of erythroblastosis virus 26 (E26V). The proteins encoded by the AMV and E26V alleles of v-myb differ from the product of c-myb in three ways: at their amino termini, they lack 71 and 80 amino acids respectively; at their carboxy termini, they are deficient in 199 and 278 residues; and 11 substitutions of amino acids are scattered throughout the product of AMV allele, whereas the product of the E26V allele contains only a single substitution. The structural origins of tumorigenicity by v-myb and the biological functions of c-myb remain enigmatic. The findings and molecular clones described here should now permit a systematic exploration of these enigmas.